Confocal laser endomicroscopy for diagnosis of Barrett's esophagus - Neumann, Helmut; Langner, Cord; Neurath, Markus; Vieth, Michael (Frontiers in Oncology, 2012)
Barrett's esophagus (BE) is established as a premalignant condition in the distal esophagus. Current surveillance guidelines recommend random biopsies every 1-2 cm at intervals of 3-5 years. Advanced endoscopic imaging of BE underwent several technical revolutions within the last decade including broad-field (red-flag) techniques (e.g., chromoendoscopy) and small-field techniques with confocal laser endomicroscopy (CLE) at the forefront. In this review we will focus on advanced endoscopic imaging using CLE for the diagnosis and characterization of BE and associated neoplasia. In addition, we will critically discuss the technique of CLE and provide some tricks and hints for the daily routine practice of CLE for diagnosis of BE. © 2012 Neumann, Langner, Neurath and Vieth.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Advanced imgaging; Barrett; Cancer; CLE; Dysplasia; Endomicroscopy; Fluorescein